Efforts to Overcome the Industrial Revolution 4.0 Through Lesson Study - Dani, Nur Rohmah; sumarni, sri; Roemintoyo, Roemintoyo; Waluyo, Waluyo (Universitas Sebelas Maret, 2023)
In recent years technology in the Industrial Revolution era 4.0 is developing very rapidly. The Industrial Revolution 4.0 is very influential in changing behavior in the world of education, business, and the industrial world. Skills and competencies become the main things that need to be considered. Besides that characteristics in the era of the Industrial Revolution 4.0 are also very influential on employment. From here, a change is needed to overcome the problem by carrying out learning activities using lesson study, which in turn can improve learning the material provided can be delivered and the objectives of learning can be achieved. This study aims to determine the development of learning innovations through lesson study on mixed methods. The research method used is descriptive qualitative. The results of the study stated that students were ready with the efforts to face the Industrial Revolution 4.0.